Current status of onboard carbon capture and storage (OCCS) system: A survey of technical assessment - Tianyang Zhao; Run Li; Zezhou Zhang; Chunfeng Song (Carbon Capture Science & Technology)
As the global greenhouse effect worsens every year, controlling greenhouse gas (GHG) emissions, particularly carbon dioxide (CO2), has become a key issue. The shipping industry, as a major component of the transportation industry, has a sizable percentage share in global CO2 emissions. Further development and improvement of Onboard Carbon Capture and Storage (OCCS) technology is required to realize the mass production of clean ships. This study focuses on the current research status of technologies related to onboard carbon capture systems, while reporting and analysing on-board carbon transport and storage systems. For onboard carbon capture technology, the development and application of different carbon capture technologies in the shipping industry are analysed and the challenges of implementing onboard carbon capture technology are discussed. In the area of onboard carbon transport and storage, a systematic description of how to regulate and realize the concentration and other characteristics of captured CO2 in pilot and large-scale applications is presented. On the basis of existing research, the current technological bottlenecks and future perspectives of OCCS systems are also presented, based on existing research, with the aim of analysing the solutions for controlling CO2 emissions from ships and providing perspectives for their sustainable development in the future.